Pelatihan digital marketing dan pemanfaatan e-commerce untuk optimalisasi penjualan UMKM Keripik Sukun Holifah Sari Pajarakan - Umi Diantika Susilowati; Nur Agustina Khatijah; Nabila (P3HKI - Universitas Muhammadiyah Parepare, 2024)
The micro, small, and medium enterprise (MSME) Keripik Sukun Holifah Sari in Pajarakan has been facing challenges in boosting sales due to limited market access and a lack of understanding of digital technology, particularly e-commerce. This community engagement program aims to enhance the entrepreneurial capacity of MSME actors by utilizing e-commerce platforms and digital marketing strategies to optimize product sales. The methods employed include training sessions, technical assistance, and evaluations through interviews and direct observation. The results indicate a significant improvement in the entrepreneurs’ understanding of online store account creation, product content management, and the use of social media for promotional activities. Furthermore, the intervention resulted in an average sales increase of 30% over three months compared to the previous period. This initiative demonstrates that leveraging e-commerce and digital marketing serves as an effective solution to improve the competitiveness of MSMEs in the digital economy. It is expected that similar programs can be replicated across other MSMEs to stimulate local economic growth.